Concordancia entre los valores Z de los indicadores de crecimiento obtenidos con las referencias OMS 2006 y NCHS 1978 en niños de 6 a 60 meses de Antioquia-Colombia, 2006 (2008)
ABSTRACT: to establish the concordance between the Z scores of weight for age, length/height for age and weight for length/height from the 2006 WHO and 1978 NCHS growth standards for children under five years of age. Methods: this is cross- sectional study. Sample: subjects were randomly selected which were participating in a Food Complementation Program in Antioquia (n=2.290). The anthropometric indicators were calculated using the WHO and NCHS growth standard references. The intraclass correlation coefficient was used to estimate the concordance between the growth standards and the concordance was calculated using the Bland and Altman method. Results: there was a high and significant correlation between 2006 WHO Z scores and 1978 NCHS growth standards. The intraclass correlation coefficient showed also a high concordance values. The Bland and Altman method confirm an average difference in Z scores for weight/height of 0, 30 (CI95% -0, 09 and 0,698) and for weight for age of 0.21 (CI95% -0, 12; 0,532). Conclusion: the 2006 WHO and 1978 NCHS growth standards demonstrate a high correlation and concordance, although they are no exchangeable due to the concordance limits do not include the established ranges for this study.